Spatial scale problems and geostatistical solutions: a review. - Atkinson, Peter M.; Tate, Nicholas J. (Professional Geographer, 2000)
The writers discuss the ways in which geostatistical techniques, and to a lesser extent fractal techniques, can be employed to address several problems of data and model scaling. They draw on recent literature dealing with scale problems in geography and highlight the geostatistical operation of regularization. They note how important spatial scale is in geography and introduce scales of measurement. They examine the modelling of spatial variation and scales of variation in spatial data, paying particular attention to models of second-order properties. They conclude with a discussion of some approaches to altering the scales of measurement.